THE EFFECT OF MICRO FINANCING ON BUSINESS DEVELOPMENT AFTER GETTING FINANCING : (CASE STUDY ON MICRO CUSTOMERS PT BANK SYARIAH INDONEIA KCP KLENDER) - Nurul Subhi; Fajri Ryan Isnandar (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
The development of the potential UMKM in indonesia cannot be separated from the support of bank in the distribution of financing to UMKM actors. The role of islamic banking in developing community business, especially UMKM, is to participate in providing financing to the community to the development their business. The purpose of this study is to determine the effect of microfinance on the business development of PT Bank Syariah Indonesia KCP Klender customers and to determine the difference in customer sales turnover before and after receiving financing. The research methodology used is a quantitative approach. The results of the research conducted indicate that microfinance has a significant effect on the development of the costumer’s business. Microfinance has a significant effect on the business development of customers PT Bank Syariah Indonesia KCP Klender, seen from the results of data processing the value of the coefficient of determination R= 0.919 and R²= 0.844. This means that 84% of the micro financing variables of PT Bank Syariah Indonesia KCP Klender effect business development, and the remaining 16% is influenced by other variables or factors.